Two decades of fire-induced albedo change and associated short-wave radiative effect over sub-Saharan Africa - Flegrova,M; Brindley,H (Journal of Geophysical Research (JGR): Atmospheres, 2025)
We present an analysis of 20 years of fire and albedo data in Africa. We show that, in the mean, the subSaharan Africa postfire surface albedo anomaly can be parameterized using an exponential recoveryfunction, recovering from a decrease of 0.019 ± 0.001 immediately after a fire with a time constant of34.0 ± 0.4 days. Although the magnitude of albedo changes shows large spatial and temporal variations and a strong land cover type (LCT) dependency, exponential recovery is observed in the majority of LCTs. We show that fires cause longterm surface brightening, with an Africawide albedo increase of (9.5 ± 0.2) × 10− 410 months after a fire, but we find this is driven almost exclusively by slow vegetation recovery in the Kalahariregion, confirming previous findings. Using downward surface shortwave flux (DSSF) estimates, we calculatethe fireinduced surface radiative forcing (RF), peaking at 5 ± 2 Wm− 2 in the burn areas, albeit with a significantly smaller effect when averaged temporally and spatially. We find that the longterm RF in months 5–10 after a burn averaged over the continent is negative because of the brightening observed. Despite a welldocumented reduction in burning in Africa in the recent decades, our temporal analysis does not indicate adecrease in the overall fireinduced RF likely due to large interannual variability in albedo anomaly and DSSFdata. However, we observe a decline in the shortterm RF in southern hemisphere Africa, driven by both areduction in fires and changes in LCT distributions.